Research of Dynamic Characteristic of Rigid-flexible Coupled Toroidal Planetary Worm Drive - Yu Taoxi Hong Mei (Jixie chuandong)
In order to realize the dynamic response of spherical roller toroidal planetary worm drive, considering the independent motion of the rolling element and the stiffness of the bearing, the rigid body dynamics model of the transmission is established, and the thin-walled toroidal stator is flexibly reinforced by finite element software. A rigid-flexible coupled dynamics model is established. The system contact stiffness excitation and error excitation are quantitatively analyzed, and the dynamic response of the rigid body model and the coupled model under internal excitation is compared. The results show that due to the introduction of flexible parts, the coupled model will have sliding teeth and tooth skipping phenomenon, and the vibration is more severe than the rigid body model. The alternating sudden change of the roller speed and the high-speed rotation when not in contact will aggravate the vibration of the transmission system. The coupled model has a higher resonance frequency than rigid body model, the internal excitation has a modulation effect on the frequency response. This study provides a reference for the optimization design of the toroidal planetary worm drive dynamics.